Low satisfaction of clients for the health service provision in West Amhara region, Ethiopia - Derebe, Mulatu Melese (PLoS One, 2017)
INTRODUCTION: Client satisfaction is a key indicator to measure quality of healthcare and provides information on the level of success forproviders whether client expectations and values are met. Although there are some institutional based studies done in Ethiopia, still client satisfaction in our settings is not well addressed. Thus, this study was aimed to assess client satisfaction level and identify the underlying factors of poor health service provision in West Amhara, Ethiopia. METHODS: A cross-sectional study design was conducted from July to August, 2013. A structured questionnaire was used to collect data from 422 outpatient diagnosis (OPD) service users. The data were entered into EPI Info version 3.5.2 and analyzed usingSPSS version 16. RESULTS: Among the 422 study participants, 234 (55.5%) males, the mean (±SD) age was 37.3 (±16.4) years. The overall satisfaction level of the study participants was 39.3%. Poor cleanliness of the facility, fewer service access provision, lack of prescribed drugs within the facility and longer waiting time to get the health care service wasreported by 73.2%, 67.8%, 65.6% and 59.2% of the clients respectively. Paying service users (AOR: 2.03, 95% CI: 1.22–3.39, P: 0.007), divorced clients (AOR: 4.26, 95% CI: 1.11–16.26, P: 0.034) and hospital users (AOR: 2.18, 95% CI: 1.29–3.69, P: 0.004) were more dissatisfied. CONCLUSIONS: Client satisfaction was lowin the health provision in West Amhara region. Expansion of health facilities in remote areas, maintaining continuous availability of prescribed drugs, improving cleanliness of health facilities, and fast health service provision are recommended to satisfy clients in the setting.